Marketing Strategy for Creative Industry (Indie Video Game) (Case Study : Pamali Game by Story Tale Studio) (The Indonesian Journal of Business Administration, 2020)
Video games are a creative industry that promises high profits. In this case the video games made by Indie Studio also have the potential to generate quite high profits. In this case, Studio Story Tale with their latest and flagship product, PAMALI: Indonesian Folklore Horror, which was just released at the end of 2018, has so far released their latest content in two DLCs.This study aims to help the Story Tales Studio in knowing what factors can influence the behavior of buyers' decisions to buy Pamali games by analyzing internal factors using STP and marketing mix followed by analyzing external factors using Competitor Analysis, Consumer Analysis, PEST analysis, and Porter Five Force Analysis. The research methodology is quantitative by distributing questionnaires to respondents who like to play games to determine the factors that influence the respondent's decision to buy Pamali games.By using Multiple Linear Regression, the results show that the main factors affecting consumer decisions to buy games are personal motivation (needs) and culture (culture) followed by products, places , promotions, and Price by that using the SOSTAC framework, Story Tale Studios can implement digital marketing optimization strategies, promotion through influencers and online media, and promotion of horror culture in Indonesian culture.Keywords: Consumer Motivation, Marketing Strategy, Video Game, SWOT, SOSTAC, TOWS